1996
DOI: 10.1021/om9500937
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Bonds between Main-Group Elements and Transition Metals. 152.1 Hydrolysis and Polymerization−Precipitation of Methyltrioxorhenium in Aqueous Solution

Abstract: Methyltrioxorhenium, CH 3 ReO 3 (1; MTO), hydrolyzes rapidly in basic aqueous solutions and much more slowly in acidic media. At low concentrations (c MTO < 8.0 × 10 -3 M) the formation of CH 4 gas and perrhenate was detected. The hydrolysis was followed by spectrophotometry, and the rate constants were determined as a function of temperature and pressure according to the rate lawThe rate constant, activation enthalpy, entropy, and volume at 298.2 K are as follows:) 15.9 ( 1, ∆S 1 q /J mol -1 K -1 ) -135 ( 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…[35] Irrespective to the experimental conditions (CH 4 pressure, pH, temperature, reaction time), MTO decomposition in water is not a reversible reaction.…”
Section: Mto In Water and Water-mixed Solventsmentioning
confidence: 99%
“…[35] Irrespective to the experimental conditions (CH 4 pressure, pH, temperature, reaction time), MTO decomposition in water is not a reversible reaction.…”
Section: Mto In Water and Water-mixed Solventsmentioning
confidence: 99%
“…At higher concentrations a second reaction, a faster reversible polymerization-precipitation, takes place to yield a golden colored solid of the empirical composition {H 0.5 [(CH 3 ) 0.92 ReO 3 ]} (poly-MTO) in about 70% yield (Eq. (1)) [31][32][33][34][35][36] follows first-order reversible kinetics. The rate of polymerization-precipitation is independent of the concentration of H + , and the reaction does not occur in the presence of oxidants [31].…”
Section: Behavior Of Methyltrioxorhenium In Watermentioning
confidence: 99%
“…The identification of the compound responsible for this vibration was hampered by the limited spectroscopic information, [47] but the calculation of the IR spectra of a number of possible Re compounds revealed that only ReO 4 À and ReO 3 (diolate) À displayed a strong band close to the correct wavenumber, and the unknown compound was concluded tentatively to be a hydrolyzed rhenium species. The hydrolysis of CH 3 ReO 3 to ReO 4 À is a well-established reaction-at least in aqueous solutions [48][49][50] -and the related complex Cp*ReO 3 is converted into perrhenate ions in nonaqueous solvents in the presence of oxygen. [51] Although some differences in reactivity have been found upon comparison of CH 3 ReO 3 and various perrhenate salts, they are minor and are presumably the result of different solubilities and beneficial or detrimental effects of the counter ions.…”
mentioning
confidence: 99%